Amperometric determination of endoglin in human serum using disposable immunosensors constructed with poly(pyrrolepropionic) acid-modified electrodes. (1st December 2018) - Martínez-Periñán, E.; Sánchez-Tirado, E.; González-Cortés, A.; Barderas, R.; Sánchez-Puelles, J.M.; Martínez-Santamaría, L.; Campuzano, S.; Yáñez-Sedeño, P.; Pingarrón, J.M.
Abstract: An amperometric immunosensor for the determination of the biomarker endoglin (CD105) to comply with the requirements of sensitivity and accuracy demanded in clinical practice is reported in this work. The immunosensing platform is implemented onto disposable electrodes modified with poly(pyrrolepropionic) acid (pPPA). The methodology involves a sandwich configuration and labeling of the biotinylated detector antibody with poly-HRP-streptavidin for signal amplification. Amperometric detection of hydrogen peroxide reduction in the presence of HQ was employed as analytical readout. The different steps involved in the immunosensor preparation were monitored by electrochemical impedance spectroscopy. The resulting immunosensor provided a linear range between 0.18 and 20 ng mL −1, adequate for the determination of CD105 in serum, with a detection limit (LOD) of 140 pg mL −1 . These analytical characteristics improve those reported previously for other electrochemical immunosensors. A good reproducibility of the measurements, an excellent storage stability of the anti-CD105-pPPA/SPCE bioplatforms and an excellent selectivity of the resulting immunosensors were found. The usefulness of the immunosensors was tested by analyzing human serum samples collected from healthy individuals and patients of colorectal, breast and lung cancer and epidermolysis bullosa. The results were successfully validated against those provided by an ELISA kit. Graphical abstract: Amperometric immunosensing platform, implemented onto a disposable electrode modified with pPPA and involving a sandwich configuration for sensitive and accurate determination of CD105 in serum samples from cancer or epidermolysis bullosa patients with minimal sample treatment.